2015
DOI: 10.1186/s13636-015-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Speech signal modeling using multivariate distributions

Abstract: Using a proper distribution function for speech signal or for its representations is of crucial importance in statisticalbased speech processing algorithms. Although the most commonly used probability density function (pdf) for speech signals is Gaussian, recent studies have shown the superiority of super-Gaussian pdfs. A large research effort has focused on the investigation of a univariate case of speech signal distribution; however, in this paper, we study the multivariate distributions of speech signal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Though this result is hardly surprising, it is more specific than prior works such as [8,9,10], since we include the contribution of the speech production model and can evaluate phoneme groups separately.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Though this result is hardly surprising, it is more specific than prior works such as [8,9,10], since we include the contribution of the speech production model and can evaluate phoneme groups separately.…”
Section: Discussionmentioning
confidence: 63%
“…Selection of the best probability distribution model is therefore important for the efficiency of the algorithms, whereby many have investigated the issue [8,9,10]. In general, Gaussian models and mixture models thereof are appealing due to their analytic and computational properties, but practice have shown that in many cases the Laplacian distribution is a more accurate model of many representations of speech signals.…”
Section: Introductionmentioning
confidence: 99%
“…In the joint pdf of the Student's t distribution, the leptokurtic nature and the variance of distribution can be adjusted by tuning the degrees of freedom parameter ν [30]. When the ν parameter is set to a lower value, the tails of the distribution becomes heavier and if ν is increased to infinity, the Student's t distribution tends to a Gaussian distribution [19,20].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Motivated by the central limit theorem, the complex Gaussian model was used for both DFT clean speech and noise components. Later studies show that while noise components can be appropriately modeled by Gaussian distributions, clean speech components in the decorrelated domains are more accurately described by super-Gaussian distributions such as Laplacian (doublesided Exponential) [18], [21], [22]. Thus, employing a super-Gaussian speech prior instead of the Gaussian can improve the performance of MMSE STSA estimators [18], [22]- [24].…”
Section: Introductionmentioning
confidence: 99%
“…Later studies show that while noise components can be appropriately modeled by Gaussian distributions, clean speech components in the decorrelated domains are more accurately described by super-Gaussian distributions such as Laplacian (doublesided Exponential) [18], [21], [22]. Thus, employing a super-Gaussian speech prior instead of the Gaussian can improve the performance of MMSE STSA estimators [18], [22]- [24]. In particular, Hendriks et al [6] derived an MMSE LSA estimator under the assumption that the clean speech DFT amplitudes are following a one-sided chi distribution.…”
Section: Introductionmentioning
confidence: 99%